2017
DOI: 10.1093/occmed/kqx077
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Lost-time injuries in the US mining industry

Abstract: This is the first systematic review of lost-time injuries in the US mining sector. The results support the need for further research on factors that contribute to workplace lost-time injuries as there is limited literature on the topic. Safety analytics should also be applied to uncover new trends and predict the likelihood of future incidents before they occur. New insights will allow employers to prevent injuries and foster a safer workplace environment by implementing successful occupational health and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Working in mines exposes miners to a dangerous and toxic work environment, with most exposures leading to chronic diseases of the cardiac, respiratory, and renal systems 7‐11 . Earlier studies have documented increased occurrence of cancer, 12‐14 diabetes, 15,16 and accidental injuries 17,18 among miners. In the United States, there has been a substantial decline in occupational injuries in the mining industry since the passage of the 1969 Federal Coal Mine Health and Safety Act 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Working in mines exposes miners to a dangerous and toxic work environment, with most exposures leading to chronic diseases of the cardiac, respiratory, and renal systems 7‐11 . Earlier studies have documented increased occurrence of cancer, 12‐14 diabetes, 15,16 and accidental injuries 17,18 among miners. In the United States, there has been a substantial decline in occupational injuries in the mining industry since the passage of the 1969 Federal Coal Mine Health and Safety Act 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there is regulatory oversight within the U.S. mining industry to require near miss reporting, it is well known that underreporting occurs in the industry [Nowrouzi-Kia et al 2017]. However, many mine sites, including those who participated in the study, do have informal and formal near miss reporting procedures and forms that encourage workers to complete any near miss observed, prevented, or fixed on site.…”
Section: Worker Hands Performancementioning
confidence: 99%
“…Occupational injuries are a significant problem in the mining industry [ 1 ]. The Mine Safety and Health Administration (MSHA) reported that there were a total of 16,394 non-fatal lost time injuries in the US from 2015 to 2018 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%